The Impact of Artificial Intelligence Applications on Promoting Sustainable Marketing An Analytical Field Study at Asiacell - Iraq (Al-Mansour Journal, 2026)
This study examines the role of artificial intelligence (AI) applications in enhancing sustainable marketing by analyzing the impact of artificial neural networks, expert systems, and intelligent agents on its environmental, social, and economic dimensions. A descriptive-analytical approach was adopted, and data were collected through a questionnaire from a purposive sample of (80) employees at Asiacell Telecommunications Company in Iraq. Data were analyzed using SPSS (V.25), employing descriptive statistics, Spearman correlation, and simple regression analysis.The findings revealed a significant positive relationship and effect between AI applications and sustainable marketing, with a correlation coefficient of (0.71) and a coefficient of determination (R²=0.51). The study’s originality lies in providing empirical evidence from the Iraqi telecommunications sector on the role of AI applications in supporting sustainable marketing practices.
Keywords: Artificial intelligence; sustainable marketing; smart agents; neural network; Asia cell